Radiative habitable zones in martian polar environments - Córdoba-Jabonero, Carmen; Zorzano, María-Paz; Selsis, Franck; Patel, Manish R.; Cockell, Charles S. (Icarus (New York, N.Y. 1962), 2005)
The biologically damaging solar ultraviolet (UV) radiation (quantified by the DNA-weighted dose) reaches the martian surface in extremely high levels. Searching for potentially habitable UV-protected environments on Mars, we considered the polar ice caps that consist of a seasonally varying CO 2 ice cover and a permanent H 2O ice layer. It was found that, though the CO 2 ice is insufficient by itself to screen the UV radiation, at ∼1 m depth within the perennial H 2O ice the DNA-weighted dose is reduced to terrestrial levels. This depth depends strongly on the optical properties of the H 2O ice layers (for instance snow-like layers). The Earth-like DNA-weighted dose and Photosynthetically Active Radiation (PAR) requirements were used to define the upper and lower limits of the northern and southern polar Radiative Habitable Zone (RHZ) for which a temporal and spatial mapping was performed. Based on these studies we conclude that photosynthetic life might be possible within the ice layers of the polar regions. The thickness varies along each martian polar spring and summer between ∼1.5 and 2.4 m for H 2O ice-like layers, and a few centimeters for snow-like covers. These martian Earth-like radiative habitable environments may be primary targets for future martian astrobiological missions. Special attention should be paid to planetary protection, since the polar RHZ may also be subject to terrestrial contamination by probes.